Histone Acetylation and Chromatin Remodeling Are Required for UV-B–Dependent Transcriptional Activation of Regulated Genes in Maize - Casati, Paula (American Society of Plant Biologists, 2008)
The nuclear proteomes of maize (Zea mays) lines that differ in UV-B tolerance were compared by two-dimensional gel electrophoresis after UV light treatment. Differential accumulation of chromatin proteins, particularly histones, constituted the largest class identified by mass spectrometry. UV-B–tolerant landraces and the B73 inbred line show twice as many protein changes as the UV-B–sensitive b, pl W23 inbred line and transgenic maize expressing RNA interference constructs directed against chromatin factors. Mass spectrometic analysis of posttranslational modifications on histone proteins demonstrates that UV-B–tolerant lines exhibit greater acetylation on N-terminal tails of histones H3 and H4 after irradiation. These acetylated histones are enriched in the promoter and transcribed regions of the two UV-B–upregulated genes examined; radiation-sensitive lines lack this enrichment. DNase I and micrococcal nuclease hypersensitivity assays indicate that chromatin adopts looser structures around the selected genes in the UV-B–tolerant samples. Chromatin immunoprecipitation experiments identified additional chromatin factor changes associated with the nfc102 test gene after UV-B treatment in radiation-tolerant lines. Chromatin remodeling is thus shown to be a key process in acclimation to UV-B, and lines deficient in this process are more sensitive to UV-B.